2020
DOI: 10.1080/19942060.2019.1706639
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on geometric configurations affecting seepage from unlined earthen channels and the comparison with field measurements

Abstract: In this study, a numerical simulation is applied to investigate the effective factors on the seepage from the earthen channels. To authenticate the information at hand, some of the earthen channels in the Zayandeh-Rud irrigation network in Iran and Gediz watershed in Turkey were studied. 246 numerical models, including different sections of trapezoidal, rectangular and triangular earthen channels, were performed using the finite elements method (FEM). The results showed that, for a numerical simulation, a widt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Aghdam et al [32] and Taran and Mahtabi [23] used SEEP/W and showed that drainage pipes could reduce the uplift force for a gravity dam. Salmasi and Abraham [33] and Hosseinzadeh et al [8] used SEEP/W to predict the seepage from earthen channels at the Zayandeh-Rud irrigation channels, Iran. References [34][35][36][37] found that SEEP/W is a good tool to simulate the seepage from surface water to soil and vice versa.…”
Section: Numerical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Aghdam et al [32] and Taran and Mahtabi [23] used SEEP/W and showed that drainage pipes could reduce the uplift force for a gravity dam. Salmasi and Abraham [33] and Hosseinzadeh et al [8] used SEEP/W to predict the seepage from earthen channels at the Zayandeh-Rud irrigation channels, Iran. References [34][35][36][37] found that SEEP/W is a good tool to simulate the seepage from surface water to soil and vice versa.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…El-Molla [31] used the SEEP/W model to estimate the impact of a compacted earth lining on seepage from trapezoida irrigation canals and concluded that a highly compacted earth lining could save 99.8% o the percolated water to the aquifer. Aghdam et al [32] and Taran and Mahtabi [23] use SEEP/W and showed that drainage pipes could reduce the uplift force for a gravity dam Salmasi and Abraham [33] and Hosseinzadeh et al [8] used SEEP/W to predict the seepag from earthen channels at the Zayandeh-Rud irrigation channels, Iran. References [34-37 found that SEEP/W is a good tool to simulate the seepage from surface water to soil an vice versa.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…According to the soil parameters in Figure 4, the soil for calculations was considered to be Bingham material (Asl et al, 2020). The characteristics of this material are incompressible, isotropic and homogeneous.…”
Section: Soil Modelmentioning
confidence: 99%
“…(1) In terms of the tilling procedure of ploughbreast, so many soils enter the ploughbreast surface through the ploughshank, particularly its intermediary section, along which the severe flowing interaction occurs because of ploughshank inverting and cutting the soil layers. (2) In terms of the tilling behaviors of plough-breast, the soil-tool interaction encounters dynamics flow along the ploughshank (Asl et al, 2020;. This flowing interaction leads to more violent as the tilling depth/ tillage speed is increased.…”
Section: Effects Of the Tillage Speedsmentioning
confidence: 99%
“…Current situation makes lining of irrigation network compulsory in the province to avoid loss of fresh water via seepage into brackish groundwater. Reducing conveyance losses using appropriate techniques will protect land degradation from waterlogging and salinization, minimize irrigation return flows, reduce mobilization of salts and other trace elements into the streams, protect water quality for downstream usage of lower riparian, no non-beneficial losses of fresh water, decrease water table and conserve water for other beneficial services, decrease drainage requirements, increase water use efficiency (WUE) and enhance crop yields resulting in more cropping intensities [15,16]. Reducing seepage losses by some effective interventions, such as canal lining, is the best way to reduce climate change impacts while still maintaining food security; this is one strategy for making our agriculture more competitive and productive.…”
Section: Introductionmentioning
confidence: 99%